2009
DOI: 10.1186/1897-4287-7-5
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of BRCA1, but not CHEK2 or NBS1 (NBN), founder mutations in Russian ovarian cancer patients

Abstract: Background: A significant portion of ovarian cancer (OC) cases is caused by germ-line mutations in BRCA1 or BRCA2 genes. BRCA testing is cheap in populations with founder effect and therefore recommended for all patients with OC diagnosis. Recurrent mutations constitute the vast majority of BRCA defects in Russia, however their impact in OC morbidity has not been yet systematically studied. Furthermore, Russian population is characterized by a relatively high frequency of CHEK2 and NBS1 (NBN) heterozygotes, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 46 publications
2
24
0
2
Order By: Relevance
“…This founder mutation has been reported in 70 to 90% of Jewish families with high risk of breast and ovarian cancer [14]. The highest prevalence of this BRCA1 mutation has been observed in Eastern European countries (reaching 30 to 40%) such as Poland [15], Russia [16], Hungary [17] and Greece [18]. Less prevalence has been seen in Germany [19] and Italy [20] but it has not been found in Spanish population [21] nor in Moroccan [22] and Algerian populations [23].…”
Section: Discussionmentioning
confidence: 97%
“…This founder mutation has been reported in 70 to 90% of Jewish families with high risk of breast and ovarian cancer [14]. The highest prevalence of this BRCA1 mutation has been observed in Eastern European countries (reaching 30 to 40%) such as Poland [15], Russia [16], Hungary [17] and Greece [18]. Less prevalence has been seen in Germany [19] and Italy [20] but it has not been found in Spanish population [21] nor in Moroccan [22] and Algerian populations [23].…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, the meta-analyses published by Weischer et al (2008) showed that CHEK2 1100delC is an important breast cancer predisposition factor, increasing the risk by three-to five-fold. Studies carried out in Poland and neighboring countries shows that this mutation occurred in 0.0-5.2% breast cancer patients versus 0.0-0.92% in controls (Dufault et al 2004;Kleibl et al 2005;Rashid et al 2005;Kwiatkowska et al 2006;Cybulski et al 2007a;Fedorova et al 2007;Sokolenko et al 2007;Suspitsin et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…BRCA1/2 testing was initiated at the N.N. Petrov Institute of Oncology (St Petersburg, Russia) in 2007 as part of research activities 9. All ovarian cancer patients were tested for recurrent Slavic mutations 10.…”
Section: Methodsmentioning
confidence: 99%